MEMAKNAI KEMBALI KANTOR URUSAN AGAMA: PENCATATAN PERKAWINAN UNTUK SEMUA AGAMA DI KUA INKLUSIF - Meliesa Permatahati; Sonny Dewi Judiasih; Hazar Kusmayanti; Deden Sumantry (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Marriage data disparity between marriage registration agency and the people reluctivity to register their marriage due to inaccessibility of Civil Registration Office are few marriage registration problems in Indonesia, therefore the Ministry of Religion brought the idea to provide services for all religions through KUA Inklusif. The main concern in this article is the authority and the possibility of KUA as a one-stop service for all religion marriage registration. This research uses a normative juridical approach method by examining library materials or secondary data. This research is descriptive analytical, describing the applicable laws associated with legal theories and the implementation related to the problems to be studied. KUA is under the auspices of the Directorate General of Islamic Community Guidance, one of whose functions is to carry out marriage registration for the Muslim community so that the KUA is not authorized to carry out marriage registration for other religions